Changes of moisture distribution and starch properties in fermented dough under subfreezing temperature storage - ZHANG,Lin (2022)
Abstract This paper took fermented dough as the research object. The difference between the subfreezing temperature and other freezing temperatures for long-term storage of fermented dough was discussed. The fermented dough was quick-frozen at -30 °C for 1 h and then stored at -6 °C, -12 °C and -18 °C for 5 d, 10 d and 15 d. The results indicated that with decreasing freezing temperature, the content of bound water in the dough increased gradually so that the water in the dough could be better preserved and the storage time of the dough could be prolonged. Although low temperatures could have a better storage effect, too low temperature and prolonged freezing time would destroy the structure of the starch in the dough. The structure of the starch stored at the subfreezing temperature (-12 °C) was better than that stored at other temperatures. Compared with the common freezing temperature (-18 °C), the subfreezing temperature not only achieves a better storage effect but also reduces energy consumption.